2014
DOI: 10.1007/s10854-014-2202-x
|View full text |Cite
|
Sign up to set email alerts
|

Boosting ZnO nanowire dye-sensitized solar cell efficiency by coating a porous ZnO layer on the nanowires

Abstract: Novel ZnO core/shell nanostructures were constructed by depositing a porous ZnO layer directly on the surfaces of pre-fabricated ZnO nanowires through a facile chemical method. The morphology and structure of the obtained products have been investigated by fieldemission scanning electron microscopy, high-resolution transmission electron microscopy and X-ray diffraction analysis. In these unique nanostructures, the porous overlayer exhibits a large surface area for sufficient dye loading to enhance light harves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Abe et al reported [49] the stabilization of coumarin and carbazole dyes through the insertion of an oligothiophene moiety between the donor and acceptor components of these dyes. Compared with the activities in dye sensitized solar cell research [46,50,51], dye sensitization for solar water splitting appears to be an area with challenging yet potentially transformational opportunities.…”
Section: Dye Sensitizationmentioning
confidence: 99%
“…Abe et al reported [49] the stabilization of coumarin and carbazole dyes through the insertion of an oligothiophene moiety between the donor and acceptor components of these dyes. Compared with the activities in dye sensitized solar cell research [46,50,51], dye sensitization for solar water splitting appears to be an area with challenging yet potentially transformational opportunities.…”
Section: Dye Sensitizationmentioning
confidence: 99%